Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Loyalitas Pelanggan Dalam Pembayaran Rekening Air PT Adhya Tirta Batam Di Kota Batam - Sitompul, Ivanali; Heryenzus (ADAI Kepri, 2022)
The purpose of this study was to identify the effect of service quality and product quality on customer loyalty in water utility billing PT.Adhya Tirta Batam. Population in this research is customer of PT. Adhya Tirta Batam which amounted to 152 people with sample of 110 people using convenience sampling. Results of data processing shows the quality of service (X1), product quality (X2) partially affect customer loyalty PT. Adhya Tirta Batam. this is indicated by the F test produced with the value 35.099 is greater than the value 3.08, this data shows > next service quality and product quality have a very strong influence in influencing customer loyalty PT. Adhya Tirta Batam. Positive and significant impact on customer loyalty, this means the better the quality of service in a company, the higher the loyalty of these customers. Product quality has a significant positive effect on customer loyalty, this means the higher the quality of existing products in the company will be higher customer loyalty in the company. Partially quality of service and product quality have positive and significant influence to customer loyalty.